Rasal1 regulates calcium dependent neuronal maturation by modifying microtubule dynamics - M. H. S. Deurloo; S. Eide; E. Turlova; Q. Li; S. Spijker; H.-S. Sun; A. J. A. Groffen; Z.-P. Feng (Cell & Bioscience, 2024)
Abstract Background Rasal1 is a Ras GTPase-activating protein which contains C2 domains necessary for dynamic membrane association following intracellular calcium elevation. Membrane-bound Rasal1 inactivates Ras signaling through its RasGAP activity, and through such mechanisms has been implicated in regulating various cellular functions in the context of tumors. Although highly expressed in the brain, the contribution of Rasal1 to neuronal development and function has yet to be explored. Results We examined the contributions of Rasal1 to neuronal development in primary culture of hippocampal neurons through modulation of Rasal1 expression using molecular tools. Fixed and live cell imaging demonstrate diffuse expression of Rasal1 throughout the cell soma, dendrites and axon which localizes to the neuronal plasma membrane in response to intracellular calcium fluctuation. Pull-down and co-immunoprecipitation demonstrate direct interaction of Rasal1 with PKC, tubulin, and CaMKII. Consequently, Rasal1 is found to stabilize microtubules, through post-translational modification of tubulin, and accordingly inhibit dendritic outgrowth and branching. Through imaging, molecular, and electrophysiological techniques Rasal1 is shown to promote NMDA-mediated synaptic activity and CaMKII phosphorylation. Conclusions Rasal1 functions in two separate roles in neuronal development; calcium regulated neurite outgrowth and the promotion of NMDA receptor-mediated postsynaptic events which may be mediated both by interaction with direct binding partners or calcium-dependent regulation of down-stream pathways. Importantly, the outlined molecular mechanisms of Rasal1 may contribute notably to normal neuronal development and synapse formation.